Microstructural and mechanical properties study of the curing process of self-compacting concrete. (15th March 2016) - Aparicio, S.; Martínez-Ramírez, S.; Ranz, J.; Fuente, J.V.; Hernández, M.G.
Abstract: A microstructural and mechanical properties study was conducted to investigate the effect of the curing conditions on the final properties of self-compacting concrete. Two different curing conditions were considered simulating the summer conditions in coastal (20 °C and 70% relative humidity, RH) and central (cycles of 40 °C) zones in Spain. Different microstructural and mechanical parameters were measured to study the hydration using different techniques: Micro-Raman spectroscopy, nuclear magnetic resonance, compressive strength and ultrasonic testing. After 7 days of hydration the central conditions produce samples with higher hydration degree than coastal conditions, but after 28 days of curing, the hydration degree was very similar in both curing conditions. This high hydration degree after 7 days conducted to a decline or stabilization in compressive strength at long curing times. The mean chain length of the C-S-H gel formed in the studied concrete was quite high comparing with other works since more Al was incorporated in the C-S-H gel. It was also obtained that for high temperatures after 7 days of curing all microstructural and mechanical parameters were quite stable meaning that high temperatures accelerate the hydration of the samples. Graphical abstract: Highlights: The mechanical properties of self-compacting concrete corroborate the microstructural parameters studied. High temperatures accelerate the hydration of SCC and conduct to a stabilization in compressive strength at long times. High mean chain lengths values of C-S-H gel formed in SCC were obtained due to high aluminum content. Micro-Raman spectroscopy is a useful technique to study hydration of concrete.